(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Gender studies are among the important and few titles in the Arab and Islamic world, and despite its importance, there is reluctance and reluctance among researchers to delve into such titles. Perhaps one of the reasons for this reluctance is the sensitivity of these addresses on the one hand, and its difficulty on the other hand, although it may be a reason to find out the causes of many phenomena and their stages of development, and to provide scientific treatments to reduce the negative phenomena that may plague societies and throw them out of the civilization tide And it causes great damage to the social value system, and with the passage of time it turns into a norm that prevails and ravages society from the inside and strikes it at the core of its norms. To study a phenomenon of gender that recorded a presence in Islamic societies, so we wanted to shed light on it and deconstruct its symbols during its march through long history, and we do not claim that this phenomenon was widespread in the Islamic community in its medieval times, but we wanted to prove its existence through What was reported by the stories scattered in the stomachs of the sources, and what we know, it may have been spread in some way, but its sensitivity cannot be disclosed and publicly revealed, since even those who tend to it in secret may He curses and denounces her in public and rejects her in public. The phenomenon of femininity is one of the important phenomena that we can say that it is part of the gender system, and it has had ancient historical roots that may have existed since the age of man, and it is one of the negative phenomena rejected in the Islamic society, and even in the prevailing social norm in a pre-era Islam, this phenomenon was present in the ancient Assyrian and Babylonian societies, and we have referred during the search to texts confirming our saying this, that is, it is not a new phenomenon that appeared in the Islamic ages, and the Islamic religion had an opposing stance denouncing it, through the Qur’anic verses that indicated with disapproval of these The phenomenon, as well as the position of the Messenger Muhammad, may God’s prayers and peace be upon him and his family, and many companions and scholars rejected this phenomenon and fought its prevalence and spread and warned against it. Likewise was the position of the previous monotheistic religions of it. As for the social system, it is the other that categorically rejected it, and emphasized the functions and roles that are specific to each race. Of the human race, we warn against encroaching on the occupational tasks of both sexes, and to preserve what they are assigned to during the life of the individual. We focused in the research on giving transitional examples of the existence of the phenomenon in ancient history up to pre-Islamic history, then we dealt with it in Islamic history keen to be a historical study, by tracing historical texts, analyzing them, and giving judgments about them, and we dealt with the reasons that helped the existence of the phenomenon of femininity when Some, including: biological, psychological, and social, and although Islamic societies are societies about which we can say the patriarchy of sovereignty in which men are the foundation of women, while preserving full rights of women, then it is not easy to exchange biological roles for whatever reason, otherwise, an imbalance A major solution to the social system will lead to its complete collapse, and we have also highlighted that there is a difference between the real tendency resulting from a real desire for some males to convert to the opposite sex, distinguishing between this act and what is called a convention: (denial), the second means temporary harm to the owner. Until he disguises himself in women’s clothes, for example, in order to get rid of a certain situation or an imminent danger. However, effeminacy is an unbridled desire for some males to truly belong to the world of women and try to do what women do, and this This in itself is a clear confusion for the functions that biologically define each sex